Maintenance Therapy for CD20+ Indolent Lymphoma: Who Should Receive Maintenance? (Canadian Hematology Today, 2024)
Maintenance rituximab (MR) has been a mainstay of treatment in Canada for CD20‑positive indolent lymphoma for two decades. The adoption of MR into clinical practice occurred after the publication of the EORTC 20981 trial. This trial showed a significant improvement in progression free survival (PFS) with two years of MR versus observation after induction therapy with cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) or rituximab with cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) in patients with relapsed follicular lymphoma (FL). The use of MR was broadly extended to include its use in the front‑line setting, following any R-containing inductions and including all CD20-positive indolent lymphoma histologies.Automatic recommendations for MR became the standard practice for most patients. Given the recent changes to standard induction regimens in some indications, and with heightened concerns about infectious complications during B-cell depleting therapy, the recommendation for the use of MR should no longer be considered automatic. This review offers a balanced perspective of the evidence for MR.